Relevance of sustainability education in the tourism sector - León-Gómez, Ana; Mora Forero, Jorge Alexander (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
This study presents a bibliometric analysis of a total of 113 publications released between 1996 and 2021 that analyse academic training in sustainability in tourism universities worldwide. The main objective of this analysis is to identify the most relevant research in this field and the most current research trends in the Web of Science database. To this end, we carried out a review of the productivity of the most prolific authors, journals and geographical regions. This was followed by analyses of co-authorship networks and keyword co-occurrences.